The invisible Plant Technology of Prehistoric Southeast Asia: Indirect Evidence for Basket and Rope Making at Tabon Cave, Philippines, 39-33,000 Years Ago. - Xhauflaira, Hermine (Archīum Ateneo, 2023)
A large part of our material culture is made of organic materials, and this was likely the case also during prehistory. Amongst this prehistoric organic material culture are textiles and cordages, taking advantage of the flexibility and resistance of plant fibres. While in very exceptional cases and under very favourable circumstances, fragments of baskets and cords have survived and were discovered in late Pleistocene and Holocene archaeological sites, these objects are generally not preserved, especially in tropical regions. We report here indirect evidence of basket/tying material making found on stone tools dating to 39–33,000 BP from Tabon Cave, Palawan Philippines. The distribution of use-wear on these artefacts is the same as the distribution observed on experimental tools used to thin fibres, following a technique that is widespread in the region currently. The goal of this activity is to turn hard plant segments into supple strips suitable as tying material or to weave baskets, traps, and even boats. This study shows early evidence of this practice in Southeast Asia and adds to the growing set of discoveries showing that fibre technology was an integral part of late Pleistocene skillset. This paper also provides a new way to identify supple strips of fibres made of tropical plants in the archaeological record, an organic technology that is otherwise most of the time invisible.